Trace minerals and freezability of cross-bred bull semen - MOHANTY, D N; ANSARI, M R; PATRA, R C; PATTANAIK, A K (The Indian Journal of Animal Reproduction, 2023)
In the present study the effect of trace elements of semen on freezing from four good and four poor freezable crossbredbulls were investigated. The mean concentration of copper (μg/ml), cobalt (μg/ml) , zinc (μg/ml) and iron (μg/ml) in the neat seminalplasma of good freezable semen was 0.874±0.092, 0.48 I ±0.038, I 0.5 I 9±0.648 and 48.98±3.09, whereas the correspondingconcentration in the post-thaw semen samples was 0.084±0.01 I, 0.128±0.039, 2.282±0.241 and 15.73±1.06, respectively. Similarly,the concentration of the above trace minerals in the poor freezable bull semen was estimated to be 0.629±0.071, 0.341±0.037,5.065±0.446 and 45.45±2.60 in neat and 0.066±0.009, 0. I 03±0.023, 1.993±0.25 I and 19.00±1.01 in post-thaw semen samples.Highly significant difference (P < 0.0 I) was observed between the semen samples of good and poor freezable bulls with respect tozinc, whereas the difference with respect to copper and cobalt was significant (P < 0.05) in the neat state. The post-thawconcentration of only iron registered significant difference between the good and poor freezable semen samples.
Keywords: Freezability; crossbred; trace minerals